The growth response and hepatosomatic index of milkfish (Chanos chanos Forsskal) fed with diet various levels carbohydrates in fermented of cow rumen liquid - Andi Masriah (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
One effort to reduce the role of protein as an energy source in feed is to maximize the use of feed carbohydrates as an energy source and engineering optimization of feed utilization can be done by adding exogenous digestive enzymes to feed. This study aims to determine the level of carbohydrates in the feed after being given cow rumen liquid which gives the best growth response and hepatosomatic index in milkfish. This study was designed using a completely randomized design (CRD) consisting of 4 treatments and 3 replications, Thus, there are 12 experimental units. The treatments were feeding with different levels of carbohydrate feed, namely 27,81; 39,50; 46,97 and 56,75% mixed with 80 mL of rumen liquid per 100 g of feed. Feed was given to juvenile milkfish measuring 7.19Â±0,036 g which was kept in a recirculating aquarium with a density of 15 fish/45 L of brackish water. The provision of various levels of carbohydrates in the feed had an effect (Î±<0.05) on relative growth and survival but had no effect (Î±>0.05) on the hepatosomatic index of milkfish. Statistically, the best relative growth response and survival were found in fish fed with a carbohydrate-level feed treatment of 27,81; 39,50; 46,97%.